Climate readiness indicators for agriculture - Wollenberg, Eva Karoline; Zurek, M.; Pinto, Alex de (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Countries vary in their institutional technical and financial abilities to prepare for climate change in agriculture and to balance food security, adaptation and mitigation goals.